Comparative Investigation of Engine Compartment Insulation Materials on ECE R51 Pass-By Noise Performance of M3 Category Buses (Aintelia Science Notes, 2026)
This study presents a comparative investigation of two insulation materials commonly used in commercial vehicle engine compartments: closed-cell polyurethane foam and polyester nonwoven felt. A comprehensive review of commercially available insulation materials was initially conducted considering both acoustic performance and regulatory requirements. Based on this evaluation, two representative insulation solutions were selected for full-scale experimental validation. Two equivalent M3 category city buses equipped with identical 220 kW rear-mounted Mercedes diesel powertrains were tested under standardized ECE R51 pass-by noise conditions. The first configuration employed closed-cell polyurethane foam, while the second utilized polyester nonwoven felt. Noise measurements were performed according to ECE R51 requirements under homologation-level test conditions. Results demonstrated that the polyester nonwoven insulation achieved a lower average pass-by noise level of 74.9 dB(A) compared to 79.5 dB(A) for the polyurethane foam configuration, corresponding to an overall improvement of approximately 4.6 dB. The improved performance was attributed to the superior sound absorption characteristics of the porous fibrous structure, particularly within the dominant engine noise frequency range of 1500–2000 Hz. The study provides practical guidance for acoustic insulation material selection in commercial vehicle applications and demonstrates the importance of considering both acoustic performance and regulatory compliance during engine compartment insulation design.
Keywords: ECE R51; ECE R107; Pass-by Noise; Acoustic Insulation; Polyester Nonwoven Felt; Polyurethane Foam; M3 Bus